Analisis Pengaruh Dana Pihak Ketiga Dan Pembiayaan Terhadap Likuiditas Bank NTB Syariah - Alda Fitriani; Rusman Azizoma (Universitas Islam Negeri Mataram, 2022)
This study aims to determine the effect of financing and third party funds on the Liquidity of Sharia NTB Bank. This type of research is quantitative research using secondary data from the financial statements of Sharia NTB Bank and analyzed and processed using SPSS. After the tests carried out by the researchers, the results showed that individually Third Party Funds had a significant positive effect on the Liquidity of Sharia NTB Bank and Financing also had a significant influence but had the opposite direction (Negative) on the Liquidity of Sharia NTB Bank. Meanwhile, simultaneously Third Party Funds and Financing together have a significant effect on the Liquidity of Sharia NTB Bank. This study provides significant academic contributions by offering empirical insights into the liquidity management of Islamic banks, specifically within Sharia NTB Bank.